2019
DOI: 10.1146/annurev-micro-020518-115617
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of the Cell Cycle in Trypanosomes

Abstract: Trypanosomes have complex life cycles within which there are both proliferative and differentiation cell divisions. The coordination of the cell cycle to achieve these different divisions is critical for the parasite to infect both host and vector. From studying the regulation of the proliferative cell cycle of the Trypanosoma brucei procyclic life cycle stage, three subcycles emerge that control the duplication and segregation of ( a) the nucleus, ( b) the kinetoplast, and ( c) a set of cytoskeletal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 154 publications
2
76
0
Order By: Relevance
“…Despite intense interest and study (13,15), many cell cycle regulators in trypanosomatids remain to be identified and much remains to be learned about cell cycle control and progression in these parasites. DNA staining followed by flow cytometry is a widely used approach for quantifying cellular DNA content and analysing cell cycle distribution across otherwise asynchronous populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite intense interest and study (13,15), many cell cycle regulators in trypanosomatids remain to be identified and much remains to be learned about cell cycle control and progression in these parasites. DNA staining followed by flow cytometry is a widely used approach for quantifying cellular DNA content and analysing cell cycle distribution across otherwise asynchronous populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the T. brucei flagellum (7) serves as a model for studies on human ciliopathies (8-11). Divergent features, shared with other pathogenic trypanosomatids, such as Trypanosoma cruzi and Leishmania, include glycolysis compartmentalised within glycosomes (12), a single mitochondrion with a complex mitochondrial DNA structure known as the kinetoplast (13) and polycistronic transcription of almost every gene (14). Widespread, and constitutive, polycistronic transcription in trypanosomatids places major emphasis on post-transcriptional controls by mRNA binding proteins (RBPs) and post-translational controls, involving protein phosphorylation in particular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell prepares for division in the rst gap phase (G 0 /G 1 ), replicates the DNA during the S phase, and then undergoes mitosis (M) in the second gap phase (G 2 ). In T. brucei, the cell cycle is tightly regulated to ensure that single-copy organelles and structures such as Golgi body, mitochondrion, kinetoplast, nucleus, basal body, and agellum are duplicated, maintained at precise positions in the cell and segregated accurately [37]. Various GO terms related to organelles were over-represented in the black module (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cell division cycle of African trypanosomes has been studied extensively (Farr and Gull, 2012;Vaughan and Gull, 2008;Wheeler et al, 2019), identifying various processes that are important for both proliferative and differentiation-linked cell division.…”
Section: Introductionmentioning
confidence: 99%